Parents Effectiveness Training (PET) as a Strategy for Improving the Interpersonal Relationship between Foster Parents and Children in Alternative Care Settings - Vetriana, Hana; Hernawati, Lucia; Eriany, RA. Praharesti (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Building effective communication between parents and children within the family can be a challenging task. This is also the case for foster mothers at SOS Children’s Village Semarang, who face unique challenges in establishing communication with their foster children from diverse backgrounds and age groups. These circumstances present specific difficulties in achieving effective interpersonal communication in their caregiving roles. This training program aims to improve the interpersonal communication skills of foster mothers when interacting with children. The training was conducted over four sessions using key concepts from the Parents Effectiveness Training (PET) program, namely Active Listening, I-Messages, the Behavior Window, and No-Lose Conflict Resolution. The training program is expected to enhance the interpersonal communication skills of foster mothers. This study employed a quantitative method using a quasi-experimental approach. The research design followed a one-group pre-test–post-test format, comparing scores before and after the intervention within the same group. The analysis results showed a significant difference between the pre-test and post-test scores (Z = -2.80, p = 0.0019 < 0.05), indicating that the PET training program had a highly significant impact and demonstrated strong effectiveness in improving the interpersonal communication abilities of foster mothers.Membangun komunikasi yang efektif antara orang tua dan anak-anak dalam suatu keluarga bukanlah hal yang mudah. Hal ini terjadi juga bagi Ibu asuh di SOS Children’s Village Semarang yang menghadapi permasalahan dalam membangun komunikasi dengan anak-anak asuh nya yang memiliki latar belakang dan rentang usia yang berbeda. Hal ini menjadi tantangan tersendiri untuk memiliki komunikasi interpersonal yang efektif saat memberikan pengasuhan. Tujuan program pelatihan ini adalah untuk meningkatkan kemampuan komunikasi interpersonal ibu asuh dalam berkomunikasi dengan anak-anak. Pelatihan dilakukan selama 4 kali pertemuan dengan menggunakan konsep kunci yang ada dalam program pelatihan Parents Effectivess Training (PET) yaitu Active Listening, I-Messages, Behavior Window dan No-Lose Conflict Resolution. Ada kemungkinan program pelatihan ini dapat meningkatkan kemampuan komunikasi interpersonal pada ibu asuh. Metode penelitian yang digunakan yaitu penelitian kuantitatif dengan pendekatan kuasi eksperimen. Desain yang digunakan adalah one group pretest-posttest, yaitu dengan membandingkan skor sebelum dan sesudah intervensi pada kelompok yang sama. Dari hasil analisis menunjukkan adanya perbedaan yang signifikan antara skor pre-test dan post-test (Z = -2.80, p = 0.0019 < 0.05), yang mengindikasikan bahwa intervensi program pelatihan PET memberikan pengaruh yang sangat signifikan dan memiliki efektivitas yang tinggi dalam peningkatan keterampilan komunikasi interpersonal ibu asuh.